Verified envenomations by crevice weaver spiders (genus Kukulcania): Bites are of minor expression but the spiders are commonly misidentified as medically important brown recluses (genus Loxosceles) in North America. (March 2022) - Vetter, Richard S.
Abstract: From southern North America, five verified bites by crevice weaver spiders, Kukulcania spp. (Filistatidae), are presented here, three of which are pediatric cases. Although the envenomation manifestations were of minimal expression, the salient aspect of this report is that Kukulcania spiders are frequently misidentified as brown recluse spiders (genus Loxosceles ) which are infamous for causing serious dermonecrosis and rarely, life-threatening systemic effects. Misidentification of this relatively harmless spider as a medically important recluse when presented to a physician in an envenomation episode could lead to unwarranted and overzealous treatment such as contraindicated debridement of the affected area. Highlights: Envenomation by Kukulcania spiders are of minor concern. More importantly is that they are often misidentified as medically important Loxosceles spiders. Misidentification by medical personnel could result in incorrect and harmful remedies.